Differences in Back Pain Before and After Giving Pregnancy Exercises to Pregnant Women Third trimester - wardani, linda; Puspita Sari, Melati; Perbawati, Dinar (LPPM Universitas dr. Soebandi, 2024)
Complaints of pain in the back of pregnant women are an inconvenience that arises in pregnant women in TM III. Pain that appears in the back is a physiological event that often occurs in pregnant women, but if it is not immediately followed up it will become a pathological problem. One way to deal with the problem of back pain is by providing pregnancy exercise intervention, where pregnancy exercise is done at least 3 times during pregnancy. Objective: To analyze the differences in back pain before and after being given pregnancy exercises to pregnant women in the third trimester at Polindes Plerean, Sumberjambe District. Method: In this research, the method used is quantitative quasi-experiment with a one group pre test and post test design. Population: the population is all TM III primigravida pregnant women totaling 27 respondents with a sample size of 12 pregnant women who experience TM III back pain whose selection used an accidental sampling technique. The statistical test used is the non-parametric Wilcoxon test. Results: The results obtained using the non-parametric Wilcoxon test with SPSS 27 obtained a p-value = 0.014 ≤ α = 0.05 so that H1 was accepted and H0 was rejected, which means there is a difference in back pain before and after being given pregnancy exercises to pregnant women in the third trimester. Conclusion: There is a significant difference in the level of pain in the back of pregnant women between before the intervention and after the pregnancy exercise intervention. Pregnant women, especially primigravidas entering the third trimester, are expected to do pregnancy exercises at least 3 times during pregnancy.